Optimizing Ex Vitro Acclimatization of Vanilla planifolia: Dynamics Effects of Substrate Composition and Indole-3-Butyric Acid (IBA) - Shyafna Aisyah Ryandjani; Karno; Rosyida; Anasrullah (Publication of the International Journal and Academic Research, 2026)
The ex-vitro acclimatization of tissue-cultured Vanilla planifolia represents a critical propagation bottleneck, characterized by high mortality due to transplant shock and underdeveloped root systems. This study evaluated the interactive effects of organic substrate composition and exogenous Indole-3-butyric acid (IBA) on the morpho-physiological establishment of vanilla plantlets. A 4 × 4 factorial experiment was conducted using a Completely Randomized Design (CRD), testing four acclimatization media (raw rice husk, rice husk charcoal, cocopeat, and fern roots) alongside four IBA concentrations (0, 100, 200, and 300 ppm). Morphological data collected at eight weeks after transplanting revealed a distinct survival-growth paradox. Highly aerated substrates, such as raw rice husk, significantly promoted vertical shoot elongation (12.23 cm) but resulted in unsustainably low survival rates (33.33%) due to insufficient hydraulic buffering. Conversely, highly retentive media like cocopeat yielded a superior survival rate (63.89%). Crucially, the application of 200 ppm IBA emerged as the definitive biochemical optimum. This targeted concentration successfully broke morphological dormancy to maximize root organogenesis, producing an average of 5.00 roots at 6.09 cm in total length. This robust root architecture functioned as a physiological sink, driving maximum leaf expansion and total fresh biomass accumulation (2.28g), whereas higher concentrations (300 ppm) induced phytotoxicity. Ultimately, this study demonstrates that combining a highly moisture-retentive substrate with a 200 ppm IBA application effectively resolves the survival-growth trade-off. This research delivers a highly reproducible, mechanistic protocol to minimize acclimatization mortality and significantly accelerate the scalable production of vigorous vanilla planting materials for the global agricultural industry.